Key Performance Indicators (KPI 1) Achievement and Development Efforts for the Bachelor of Mechanical Engineering Education Study Program with Tracer Study - Ramadani, Ali Hasbi; Kurniawan, Wahyu Dwi; Arizal, Heru; Nugroho, Yuli Sutoto; Safitri, Revi (International Journal of Current Educational Research, 2025)
Objective: The purpose of this study is to determine the profile of S1 Mechanical Engineering Education graduates and the competencies needed by graduate users. Additionally, it will be analyzed in terms of achieving Key Performance Indicators (KPI 1). Method: This research employs a qualitative descriptive approach. This research uses an instrument in the form of a questionnaire. The results of the questionnaire are then processed and analyzed in a qualitative descriptive manner. This data analysis technique involves data reduction, data presentation, and conclusion. Results: The results indicate that the required competencies encompass both soft skills and hard skills. Those who need to strengthen their graduate competencies to suit the needs of the world of work require soft skills, with the results achieving KPI 1 at 63.93%. Novelty: This study examines in depth the condition of graduates in the workforce, focusing on job suitability, soft skills, and specialized hard skills within the Mechanical Engineering Education Study Program. Analyzing soft skills and hard skills that need to be improved and maintained in curriculum development in the Mechanical Engineering education study program adjusted to the current technological developments.